Influência da seca prolongada na função berçário de estuários do estado do Ceará: efeitos sobre características populacionais de Mugil curema (Mugiliformes: Mugilidae) - Nascimento, Amanda Fontenele do (2024)
Estuarine ecosystems are important breeding, feeding, protection, and nursery environments for various species of fish, including several of fishing importance. However, estuaries in the semi-arid region of Brazil are subject to the effects of extreme climatic events and anthropogenic activities, which can affect the fundamental functions they perform, such as being a nursery for fish species. In this context, this study aimed to assess the influence of prolonged drought on the potential nursery function for the mullet species Mugil curema that occurs in three estuaries in northeastern Brazil: Choró, Curu, and Pacoti. Juvenile individuals of M. curema were collected during periods of prolonged drought and regular rainfall using beach seines and tarrafa. Afterward, the individuals were anesthetized, fixed in 10% normaldehyde, preserved in 70% alcohol, measured for their standard length (cm), and weighed (g). To test for potential differences in density (individuals/m2 and g/m2), size, (cm), and condition factor between the periods of prolonged drought and regular rainfall, t-tests and Mann-Whitney tests were conducted for each of the estuaries. A total of 798 juvenile M. curema were collected in the two periods analyzed. The estuaries of the Choró and Pacoti rivers showed no significant differences in density expressed in individuals/m2 between the periods of prolonged drought and regular rainfall. However, for the Curu River estuary there was a significant difference between the periods evaluated. For density expressed in g/m2, the Curu and Choró River estuaries showed significant differences between the periods of prolonged drought and regular rainfall, suggesting a stronger influence of drought on biomass compared to the Pacoti River estuary. As for the size analysis, the results indicate a significant variation in the average size of M. curema individuals in the Pacoti River estuary during the period of regular rainfall. The condition factor analysis revealed significant variations in the Choró and Curu river estuaries, indicating possible impacts on the nutritional status of the fish during prolonged drought. On the other hand, for the Pacoti River estuary there was no significant difference in the condition factor between the periods of prolonged drought and regular rainfall. The results of these studies indicate distinct patterns in the responses of M. curema between estuaries and the population variables assessed, which may have occurred due to differences in the specific characteristics of each estuary and climatic events, which made it impossible to generalize the effect of prolonged drought on nursery function for all estuaries. Thus, more temporal replicates are needed, including climatic periods with prolonged and normal droughts and evaluating different taxa, which should provide a broader framework for evaluating their effects on nursery function in estuaries in the semiarid region of Brazil.